Mucormycosis: A Surge in Mucorales Fungal Infection in Post – Covid Patients in Indian States and Insight into Known and Unknown Factors - S.G.Borkar, (International Journal of Global Health, 2021)
An overview of mucormycosis surge among post‑COVID patients in India. It reviews risk factors, clinical features, diagnostics, and urgent surgical and antifungal management, alongside gaps in evidence.